Crassula shanelleae (Crassulaceae subfam. Crassuloideae), species status for C. arborescens subsp. undulatifolia from the Eastern Cape province, South Africa - Smith, Gideon F. (Phytotaxa, 2026)
Most representatives of the predominantly southern African genus Crassula (Crassulaceae subfam. Crassuloideae) are miniature or small, shrubby herbs with, usually, distinctly succulent leaves and, sometimes, stems. Of the about 230 taxa recognised in the genus in the subcontinent, a very small cluster of species develop into small trees. Up to now, one of these, C. arborescens, has been recognised as consisting of two subspecies: the autonymic one and C. arborescens subsp. undulatifolia. A new status, at the rank of species, as C. shanelleae, is here published for the latter subspecies. The subspecific epithet ‘undulatifolia’ used under C. arborescens for this species is not adopted here at the rank of species to so prevent confusion with the pre-existing C. undulata. Plants of C. shanelleae are short-stemmed, densely branched shrublets with dense-leaved, rounded canopies. The elliptic to elliptic-obovate, weakly succulent leaves of the species are glaucous, like those of C. arborescens, but invariably have a wavy margin. In contrast, the leaf margins of the obovate to orbicular, distinctly succulent leaves of C. arborescens are flat. These and other differences among all three the arborescent Crassula species are recorded and all three are illustrated.